PENGARUH DOSIS PUPUK UREA DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KENAF (Hibiscus cannabinus L.) - Aminuddin, M. Imam (Universitas Islam Darul Ulum, 2017)
Planting distance associated with the area or the growing space occupied room in providing nutrient elements, water and light. Planting distance is too wide for less efficient in land use, if too narrow will happen high competition which resulted in low productivity. Plant population density can be increased until it reaches the power support environment, because the environment will eventually become a limiting plant growth. The purpose of this research is to know the influence of Urea fertilizer dosing and trunks against the kenaf plant growth and production. This research method using Random Design Group (RDG) factorial, which consists of two factors, namely: Factor i: dose Urea fertilizer (N), among others, N1 = 100 kg/ha of Urea; N2 = 200 kg Urea/ha; N3 = 300 kg/ha of Urea. While the Factor II: trunks (J) among others, J1 = x 20 cm planting distance 15 cm; J2 = planting distance 20 cm x 20 cm; J3 = planting distance 30 cm x 15 cm. The results of this research it can be concluded that there is an interaction on a combination of treatment doses of Urea and trunks on each parameter and the age of the plant. Treatment doses of 300 kg Urea/ha planting and spacing of 20 cm x 20 cm (N3J2) gives the best results on the growth of kenaf plants i.e. observations on plant height parameter, the diameter of the stem and leaves, as well as on many observations on production parameters wet weight per plant swaths of dry fibre, weight per plant samples and dry fiber weight per hide.